A bibliometric analysis of work–family balance: trends, themes, and future directions (2000–2024) - Yunshi Fang; Xiaoqing Li; Tini Maizura Mohtar; Brahim Chekima (Cogent Business & Management)
Despite the growing importance of work-family balance (WFB), the field still lacks large-scale, quantitative, and replicable review studies. To fill this gap, this paper adopts a bibliometric approach to analyze 921 relevant articles published between 2000 and 2024 from the Web of Science database. Utilizing tools such as bibliometrix (R package), VOSviewer, and CiteSpace, the study maps the academic output and knowledge structure of the WFB field. It aims to review existing research, define the foundational knowledge framework, trace frontier trends, and lay a foundation for future studies. Results reveal a significant increase in WFB-related publications in recent years. A stable network of core authors and journals has emerged, alongside international collaboration. However, the overall influence of the field has declined over the past decade, and breakthrough research remains scarce. Co-citation analysis identifies three major knowledge clusters: work-family conflict (WFC), work-family enrichment, and supportive culture. The journal co-citation network highlights the interdisciplinary potential of WFB research. Keyword co-occurrence analysis, evolution mapping, and factor analysis indicate hotspots include cross-cultural comparisons, industry strategies, gender issues, supportive culture, and outcome variables such as job satisfaction and organizational commitment. These findings help build a theoretical framework and offer insights for policymakers and business leaders.